2019
DOI: 10.1016/j.clinph.2019.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural and electrophysiological modulations induced by transcranial direct current stimulation in healthy elderly and Alzheimer’s disease patients: A pilot study

Abstract: Research highlights: 1. tDCS modulated neural activity in healthy elderly and Alzheimer's disease patients. 2. Neural modulations may depend on the interaction between tDCS polarity and neural state. 3. Neural modulations induced by tDCS were related to working memory improvements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 105 publications
3
34
0
7
Order By: Relevance
“…However, this phenomenon was not observed in the MCI group. This finding is consistent with that of prior AD studies (Cespón et al, 2019). To compare the effects of shortand long-term tDCS, Gangemi et al (2020) suggested that if brain stimulation (i.e., tDCS) can be effective with steady-state neurocognitive function over the short term, then this effect could be prolonged for 8 months.…”
Section: Alzheimer's Diseases and Mild Cognitive Impairmentsupporting
confidence: 86%
See 1 more Smart Citation
“…However, this phenomenon was not observed in the MCI group. This finding is consistent with that of prior AD studies (Cespón et al, 2019). To compare the effects of shortand long-term tDCS, Gangemi et al (2020) suggested that if brain stimulation (i.e., tDCS) can be effective with steady-state neurocognitive function over the short term, then this effect could be prolonged for 8 months.…”
Section: Alzheimer's Diseases and Mild Cognitive Impairmentsupporting
confidence: 86%
“…The results revealed that high-frequency power in the temporoparietal area and coherence at the temporalparietal-occipital junction were increased in the AD group. Stimulation was applied in the second study (Cespón et al, 2019) over the left DLPFC, and the return electrode was placed on the right shoulder, with a stimulation duration of 13 min. The working memory, P200 amplitude, and theta band brain activity in the frontal area increased after cathodal tDCS.…”
Section: Alzheimer's Diseases and Mild Cognitive Impairmentmentioning
confidence: 99%
“…Estimation of the achieved power for the recruited sample was advisable 92 , particularly when the sample size was not large 88 . A statistical power post hoc analysis was conducted by calculating the Cohen d 93 using the G*Power 3.1 software to determine the level of power that the main outcome (i.e., emotional arousal/ valence) of the present study achieved.…”
Section: Methodsmentioning
confidence: 99%
“…Four papers failed to identify a significant effect of tDCS on working memory performance. Cespón et al (41) failed to identify a significant change in reaction time on the N-back task amongst healthy older adults immediately following DLPFC stimulation, and found no unique memory benefits following stimulation [a result that appears to oppose their previous findings; (40)]. That said, anodal tDCS did result in increased P300 amplitudes (a marker of cognitive processing measured using electroencephalography), which correlated with improved accuracy.…”
Section: Working Memorymentioning
confidence: 89%
“…These are summarised in Table 1. By far the most common stimulation method was tDCS (14 papers), of which 10 studies found significant benefits on working memory performance (28,37,38,40,42,44,(46)(47)(48)(49), and 4 did not (29,41,43,45). Across all studies the region most commonly stimulated was the prefrontal cortex (PFC).…”
Section: Working Memorymentioning
confidence: 99%